2023
DOI: 10.1037/met0000467
|View full text |Cite
|
Sign up to set email alerts
|

Local minima and factor rotations in exploratory factor analysis.

Abstract: In exploratory factor analysis, factor rotation algorithms can converge to local solutions (i.e., local minima) when they are initiated from different starting points. To better understand this problem, we performed three studies that investigated the prevalence and correlates of local solutions with five factor rotation algorithms: varimax, oblimin, entropy, and geomin (orthogonal and oblique). In total, we simulated 16,000 data sets and performed more than 57 million factor rotations to examine the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Even there, when simulating sample data from such populations, a single factor will fail to fit item covariances perfectly in a given sample due to sampling error (MacCallum & Tucker, 1991), leading to some qualifications of alpha vs. omega claims. Furthermore, most empirical data are not strictly unidimensional, but are at best only approximately or essentially unidimensional, so have additional small perturbations of item covariances that preclude perfect fit of a one-factor model even in the population (e.g., minor domain factors too numerous to model, as posited by Tucker et al, 1969; see also Nguyen & Waller, 2022). Calculation of coefficient alpha using Eq.…”
Section: Psychometric Models and Their Factor Analytic Analogsmentioning
confidence: 99%
“…Even there, when simulating sample data from such populations, a single factor will fail to fit item covariances perfectly in a given sample due to sampling error (MacCallum & Tucker, 1991), leading to some qualifications of alpha vs. omega claims. Furthermore, most empirical data are not strictly unidimensional, but are at best only approximately or essentially unidimensional, so have additional small perturbations of item covariances that preclude perfect fit of a one-factor model even in the population (e.g., minor domain factors too numerous to model, as posited by Tucker et al, 1969; see also Nguyen & Waller, 2022). Calculation of coefficient alpha using Eq.…”
Section: Psychometric Models and Their Factor Analytic Analogsmentioning
confidence: 99%
“…Gradient projection can be used to rotate the factor loadings optimizing any mathematical criterion calculated from the factor loadings – enabling researchers to choose from a variety of rotation criteria. However, the user must be aware of the occurrence of local optima ( Hattori et al, 2017 , Nguyen and Waller, 2022 , Weide and Beauducel, 2019 ). In simplified terms, Gradient projection proceeds as follows: (1) Choose a random rotation matrix for a start; (2) Compute the rotated factor loadings for this starting rotation matrix; (3) Evaluate the rotation criterion for these intermediate rotated factor loadings; (4) Compute a new rotation matrix to achieve a more optimal value of the rotation criterion; (5) Re-iterate through steps (2) to (4) until the value of the rotation criterion does not change substantially any more between iterations; (6) The rotated factor loadings from the last iteration are the final rotated solution.…”
Section: Step-by-step Analysis Of An Erp Datasetmentioning
confidence: 99%
“…Fourth, we only explored the performance of EFA with Geomin rotation, although it should be highlighted again that other rotation procedures might lead to different results (Browne, 2001; Hakstian, 1971; Hakstian & Abell, 1974; Sass & Schmitt, 2010; Schmitt & Sass, 2011). Recently, Nguyen and Waller (2022) found that Geomin is more prone to converge to local minima than other rotation procedures. For the sake of the present investigation, and following the suggestion from one of the reviewers, we replicated the simulation study using EFA with Oblimin rotation and found that the results did not substantially differ from those of EFA with Geomin.…”
Section: Discussionmentioning
confidence: 99%